Application of metagenomic next-generation sequencing in the diagnosis and treatment of recurrent urinary tract infection in kidney transplant recipients - Duan, Wenjing; Yang, Yongguang; Zhao, Jingge; Yan, Tianzhong; Tian, Xiangyong (Frontiers in Public Health, 2022)
Background Rapid and accurate pathogen diagnosis is an urgent unmet clinical need for recurrent urinary tract infection (RUTI) in kidney transplant recipients (KTRs). Metagenomic next-generation sequencing (mNGS) may offer another strategy for diagnosing uropathogens but remains to be studied. Methods Nineteen KTRs with RUTI were collected in this study. The uropathogens were detected and compared by mNGS and urine culture, respectively. Modifications of the anti-infection strategy were also assessed. Results Rich and diverse pathogens were revealed by mNGS. mNGS was significantly higher than culture in total positive rate (100.0% vs. 31.6%; p < 0.01) and in identification rates for bacteria (89.5% vs. 31.6%; p < 0.01), for viruses (57.9% vs. 0; p < 0.01), and for fungi (42.1% vs. 0; p < 0.01), respectively. mNGS identified a significantly higher proportion of mixed infections than culture (89.5% vs. 10.5%; p < 0.01). The anti-infection therapies were adjusted in two (33.3%) and 12 (76.9%) cases guided by culture and mNGS, respectively. Conclusion mNGS has more remarkable etiological diagnostic performance compared with urine culture for KTRs with RUTI to guide anti-infection strategies and, in turn, protect the graft.